2011
DOI: 10.1007/s10529-011-0684-7
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic potato overproducing l-ascorbic acid resisted an increase in methylglyoxal under salinity stress via maintaining higher reduced glutathione level and glyoxalase enzyme activity

Abstract: Salt-tolerance was studied in transgenic potato. It was conferred by overexpression of ascorbate pathway enzyme (D-galacturonic acid reductase, GalUR). As genetic engineering of the GalUR gene in potato enhances its ascorbic acid content (L-AsA), and subsequently plants suffered minimal oxidative stress-induced damage, we now report on the comprehensive aptness of this engineering approach for enhanced salt tolerance in transgenic potato (Solanum tuberosum L. cv. Taedong Valley). Potatoes overexpressing GalUR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 54 publications
4
57
1
Order By: Relevance
“…The phenomenon of increased AsA was also reported in other crops including transgenic-GalUR potato (Upadhyaya et al 2011), and DHAR tomato (Li et al 2012) under salt stress conditions.…”
Section: Relative Water Content (Rwc)supporting
confidence: 60%
See 1 more Smart Citation
“…The phenomenon of increased AsA was also reported in other crops including transgenic-GalUR potato (Upadhyaya et al 2011), and DHAR tomato (Li et al 2012) under salt stress conditions.…”
Section: Relative Water Content (Rwc)supporting
confidence: 60%
“…This includes lowmolecular-mass non-enzyme antioxidant metabolites, such as ascorbic acid and various antioxidant enzymes such as SOD, CAT, APX, GR and POD (Bhatnagar-Mathur et al 2009;Miller et al 2010;Chaturvedi et al 2014). Ascorbic acid (AsA) is both a secondary metabolite and an antioxidant which interacts enzymatically and non-enzymatically and detoxifies the ROS (Upadhyaya et al 2011). Therefore, AsA is used as a reference compound in a number of studies associated with stress tolerance in plants (Lopez-Munguia et al 2011).…”
Section: Relative Water Content (Rwc)mentioning
confidence: 99%
“…3D). Upadhyaya et al (2011) reported higher activities of antioxidative enzymes in potato transgenic plants over-expressing the strawberry GalUR gene involved in ascorbic acid biosynthesis.…”
Section: Molecular Analysis Of T 1 Plantsmentioning
confidence: 99%
“…Transforming potato with GalUR gene which enhanced its ascorbic acid content, reduced the damage occurred by salt stress. Thus Upadhyaya et al [30] concluded that engineering of ascorbate pathway enzymes is a major step in the development of salt tolerant crop plants. Pretreatment of lentil seeds with ascorbic acid reduced the effects of salt stress and improved its grain yield [31].…”
Section: Discussionmentioning
confidence: 99%